“É só de brincando, tia!” racismo recreativo em apelidos, piadas e brincadeiras no ambiente escolar - Oliveira, Elissânia da Silva (2022)
This work seeks to understand how the racist images about black people disseminated and naturalized by society enter and structure themselves in the school universe in the form of humor or irreverence. It is known that humour, laughter and irreverence are builders naturalized population of Ceará. From an early age, one learns that people from Ceará have a comic and tell jokes about absolutely everything, because there is something of survival in manifest mood. To solve a problem, a joke is told, so from laughter, the burden becomes lighter. However, the joke or prank is not always relaxed, egalitarian or revolutionary. Sometimes, the joke reiterates the place of subalternity of groups, becoming a form of domination that mask racial hostilities at the same time that compromise the reputation of black people, attacking them because of their belonging. Thus, this work seeks to understand from questionnaires and applied forms, what people understand about racism, prejudice and the discrimination, as well as they perceive the occurrence of these actions in the school environment in form of humor or irreverence, notably through nicknames, jokes and jokes racists. This research is necessary to reflect on how derogatory images widespread, in social and virtual media, about blacks, have reached different individuals in the different fields of their social life, whether from a political, intellectual, affective, derived from different relationships, whether family or professional. Historically, black and black students have complained about the experiences of everyday school life, as they have been victims of a hostile school universe. Because of the racism that spreads there, many of them they are embarrassed by the laughter provoked by racist nicknames, jokes and jokes. These analyzes were used to build sequences of classes in the discipline of Sociology, that can: a) discuss racism and b) discuss the concept of racism recreational activity in Ceará from humor in Ceará. To carry out these reflections, this work suggests a didactic sequence of three classes and four workshops for teachers to use in the classroom.